Wear-resistant and heat-resistant rubber material, preparation method, rubber roller and application in spinning lyocell

By synthesizing silicon dioxide/carbon nitride composite materials in the rubber roller material and compounding with carboxylic silicone oil, antioxidants and other additives, the problems of insufficient oil resistance, heat resistance and wear resistance of existing rubber roller materials are solved, and higher wear resistance and heat resistance and longer service life are achieved.

CN118374076BActive Publication Date: 2025-04-08WUXI LANXIANG PLASTIC IND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410540262.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-04-08
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

The existing rubber roller materials have short service life during spinning, which affects the spinning quality due to insufficient oil resistance, heat resistance and wear resistance.

Method used

The silicon dioxide/carbon nitride composite material is synthesized by ultrasonic method and combined with carboxylic silicone oil, antioxidants and other additives to prepare wear-resistant and heat-resistant rubber materials.

Benefits of technology

It improves the wear and heat resistance and comprehensive performance of rubber materials, extends the service life of rubber rollers, and improves the spinning quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118374076B_ABST
    Figure CN118374076B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer composite materials, and discloses wear-resistant and heat-resistant rubber materials, preparation methods, rubber rollers and applications in spinning Lyocell. The preparation method includes: copolymerizing modified silicon dioxide / carbon nitride composite materials, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile to obtain an antioxidant; reacting hydrogenated silicone oil with modified POSS, methyl methacrylate, and a catalyst to obtain modified silicone oil; hydrolyzing the modified silicone oil to obtain carboxyl silicone oil; mixing hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black, and vulcanizing agent to obtain a wear-resistant and heat-resistant rubber material crude product, vulcanizing, and obtaining a wear-resistant and heat-resistant rubber material; composite molding the wear-resistant and heat-resistant rubber material crude product with a roller core to obtain a wear-resistant and heat-resistant rubber roller. The wear-resistant and heat-resistant rubber material has excellent wear resistance and heat resistance, excellent comprehensive performance, and the wear-resistant and heat-resistant rubber roller can be used for spinning Lyocell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, in particular to a wear-resistant and heat-resistant rubber material, a preparation method, a rubber roller and application in spinning lyocell. Background Art

[0002] Rubber rollers are important components of the drafting device of textile machinery. They can effectively control the movement of fibers during the drafting process. The quality and performance of rubber rollers will directly affect the quality of yarn. Due to the influence of various factors, the wear and tear of rubber rollers increase, the number of deformations increases, and the hardness decreases during the spinning process, causing the surface of the rubber rollers to become concave, thereby reducing the spinning quality.

[0003] Lyocell fiber is a green and environmentally friendly fiber, but because Lyocell fiber has poor spinnability during the spinning process and contains spinning oil, the anti-winding, oil resistance and wear resistance of the rubber roller will decrease after long-term use, shortening its service life and affecting the spinning quality.

[0004] Prior art, such as Chinese patent application CN113583317A, discloses a production formula for a rubber roller for lyocell fiber spinning, wherein carboxyl nitrile rubber, chloroether rubber, polyperfluoroethylene propylene resin, and fluorinated carbon black are blended and modified, and the quaternary blended modified rubber is vulcanized as the main material of the rubber roller, thereby improving the antistatic and wear resistance of the rubber roller, making the drafting holding force more stable, and the oil resistance and compression deformation resistance are suitable for a wide range of spinning varieties, extending the service life of the spinning rubber roller, and improving the spinning quality. However, in the rubber roller rubber material prepared by the method, the rubber used is carboxyl nitrile rubber, which has excellent oil resistance, but due to the high double bond content, the heat resistance and oxidation resistance are insufficient, and the service life is reduced, which limits the application of the material.

[0005] Existing technologies such as Chinese patent application CN105906885A disclose a rubber formula for a spinning rubber roller, which uses carboxylated nitrile rubber as a base material and adds a plasticizer TP-90B that has both plasticizing and antistatic effects, so that the obtained rubber has a good antistatic effect, effectively ensuring the spinning quality. However, the hydrophobicity, wear resistance, heat resistance and oxidation resistance of the rubber material prepared therefrom need to be improved, and the service life of the rubber roller is reduced, which limits the application of the material. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a wear-resistant and heat-resistant rubber material, a preparation method, a rubber roller and its application in spinning lyocell. The wear-resistant and heat-resistant rubber material has excellent wear resistance and heat resistance, and excellent comprehensive performance. The wear-resistant and heat-resistant rubber roller prepared from the wear-resistant and heat-resistant rubber material can be used for spinning lyocell.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a wear-resistant and heat-resistant rubber material comprises the following steps:

[0009] Step (1), mixing carbon nitride nanosheets, water and ethanol with ultrasound, adding hexadecyltrimethylammonium chloride and ammonia water in sequence, and continuing ultrasound. After the ultrasound is completed, tetraethoxysilane is added dropwise. After the addition is completed, a first reaction is carried out. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, washing is performed, and drying is performed to obtain a silicon dioxide / carbon nitride composite material;

[0010] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane and ethanol are mixed by ultrasonication, a regulator is added to adjust the pH value, a second reaction is performed, and after the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, washing is performed, and drying is performed to obtain a modified silicon dioxide / carbon nitride composite material;

[0011] Step (2), uniformly mixing the modified silicon dioxide / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, reacting, filtering after the reaction is completed, taking the filter cake, washing, and drying to obtain an antioxidant;

[0012] Step (3), mixing heptaphenyl caged polysilsesquioxane trisilanol with tetrahydrofuran, adding triethylamine and mixing evenly, dropping vinyltrichlorosilane solution, after the dropping is complete, performing a first reaction, after the reaction is completed, performing a second reaction, after the reaction is completed, purifying to obtain modified POSS;

[0013] The hydrogenated silicone oil, toluene and chloroplatinic acid are mixed, and modified POSS and methyl methacrylate are added to react for the first time. After the reaction is completed, the mixture is cooled, the solvent toluene is removed by rotary evaporation, and the mixture is dried to obtain modified silicone oil. The modified silicone oil is mixed with an aqueous sodium hydroxide solution, and reacted for the second time. After the reaction is completed, the mixture is cooled, a regulator is added to adjust the pH value, and the mixture is dried to obtain carboxyl silicone oil.

[0014] The hydrogenated carboxyl nitrile rubber is mixed with the carboxyl silicone oil, and the mixture is mixed with an antioxidant, magnesium stearate, and white carbon black. The mixture is further mixed with a vulcanizing agent to obtain a crude wear-resistant and heat-resistant rubber material, and the mixture is vulcanized. After the vulcanization is completed, a wear-resistant and heat-resistant rubber material is obtained.

[0015] Preferably, in the step (1), when preparing the silicon dioxide / carbon nitride composite material: the mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and ammonia water is 10-20:0.5-1:40-80:300-600, and the ammonia water is 28wt% ammonia water; the dripping time of tetraethoxysilane is 20-30min; and the first reaction conditions are: the first reaction is carried out at room temperature for 24-30h.

[0016] Preferably, in step (1), when preparing the modified silica / carbon nitride composite material: the mass ratio of the silica / carbon nitride composite material, vinyltrimethoxysilane, and ethanol is 1:8-10:100-150; the second reaction conditions are: the second reaction is carried out at a pH value of 9-10 and a temperature of 35-40°C for 2-3h.

[0017] Preferably, the conditioning agent comprises 28 wt % ammonia water.

[0018] Preferably, in step (2), the mass ratio of the modified silicon dioxide / carbon nitride composite material, the antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 8-10:11-15:5-7:3.5-4.5:100-150:0.2-0.3; and the reaction conditions are:

[0019] The reaction was carried out in a nitrogen atmosphere at 100-105°C for 5-6 hours.

[0020] Preferably, in the step (3), when preparing the modified POSS: the mixing conditions of heptaphenyl caged polysilsesquioxane trisilanol and tetrahydrofuran are: mixing in a nitrogen atmosphere at a temperature of -5-0°C; the dropping time of the vinyl trichlorosilane solution is 20-30min; the mass ratio of heptaphenyl caged polysilsesquioxane trisilanol, triethylamine, and vinyl trichlorosilane solution is 90-100:30-40:1000-1100; the first reaction conditions are: the first reaction is carried out in a nitrogen atmosphere at a temperature of 0-10°C for 1-2h; the second reaction conditions are: the second reaction is carried out at room temperature for 8-10h.

[0021] Furthermore, the vinyltrichlorosilane solution is prepared by mixing vinyltrichlorosilane and tetrahydrofuran in a mass ratio of 1:5.

[0022] Preferably, the purification operation comprises: filtering after the reaction is completed, taking the filtrate, removing the solvent tetrahydrofuran by rotary evaporation at a temperature of 50-60°C to obtain a crude reaction product, mixing and dissolving the crude reaction product with tetrahydrofuran in a mass ratio of 1:5-8, adding methanol of an equal mass to tetrahydrofuran for precipitation, filtering, taking the filter cake, and drying it at a temperature of 70-80°C for 8-10 hours.

[0023] Preferably, in the step (3), when preparing the carboxyl silicone oil: the mass ratio of hydrogenated silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 8-10:30-50:0.05:0.8-1:0.8-1; the first reaction conditions are: in a nitrogen atmosphere, at a temperature of 80-90°C for 12-16h.

[0024] Preferably, in the step (3), when preparing the carboxyl silicone oil: the mass ratio of the modified silicone oil to the sodium hydroxide aqueous solution is 2:1, and the sodium hydroxide aqueous solution is a 20wt% sodium hydroxide aqueous solution; the second reaction conditions are: the second reaction is carried out at a temperature of 80-90°C for 2-2.5h.

[0025] Preferably, the regulator includes a 1 mol / L hydrochloric acid aqueous solution, and the pH value after adjustment is neutral.

[0026] Preferably, in the step (3), the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizing agent is 100-150:5-8:10-15:5-10:5-10:5-10; the vulcanizing agent is prepared by mixing sulfur vulcanizing agent, dicumyl peroxide and zinc oxide in a mass ratio of 5-9:0.5-1:4-6; the banburying conditions are: mixing and banburying at a temperature of 110-120°C for 20-30min; the continued banburying conditions are: continuing banburying at a temperature of 110-120°C for 20-30min; and the vulcanization conditions are: vulcanization at a pressure of 10MPa and a temperature of 170-190°C for 15-25min.

[0027] Preferably, a wear-resistant and heat-resistant rubber material is prepared using the wear-resistant and heat-resistant rubber material crude product as described above.

[0028] The present invention discloses a method for preparing a wear-resistant and heat-resistant rubber roller by using the above-mentioned wear-resistant and heat-resistant rubber material crude product before vulcanization, comprising the following steps:

[0029] Add the wear-resistant and heat-resistant rubber material crude product into a twin-screw extruder and extrude it into a single-layer tube. At the same time, insert a stainless steel roller core into the center of the single-layer tube-shaped wear-resistant and heat-resistant rubber material crude product to obtain a rubber roller semi-finished product. After the rubber roller semi-finished product is vulcanized, it is polished and cut to obtain a wear-resistant and heat-resistant rubber roller.

[0030] Preferably, the vulcanization conditions are: vulcanization at a pressure of 10 MPa and a temperature of 170-190° C. for 15-25 min.

[0031] Preferably, a wear-resistant and heat-resistant rubber roller is prepared by the method for preparing the wear-resistant and heat-resistant rubber roller as described above.

[0032] Preferably, an application of the wear-resistant and heat-resistant rubber roller as described above in spinning lyocell.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] Hydrogenated carboxyl nitrile rubber is made by selective hydrogenation of conjugated diene, acrylonitrile and unsaturated carboxylic acid ternary copolymerization. The carboxyl group increases the polarity of the nitrile rubber and works together with the acrylonitrile chain segment in the nitrile rubber to further improve the oil resistance and strength of the rubber. In addition, since the double bond content in the nitrile rubber is reduced after selective hydrogenation, the hydrogenated carboxyl nitrile rubber has better mechanical properties and oil and heat resistance than nitrile rubber.

[0035] In the present invention, silicon dioxide is in-situ grown on carbon nitride by a sol-gel method to obtain a silicon dioxide / carbon nitride composite material. The introduction of silicon dioxide improves the hardness of carbon nitride and constructs a rough microscopic interface on the surface of carbon nitride, thereby improving its compatibility with the rubber matrix. At the same time, the heat resistance of silicon dioxide and the thermal conductivity of carbon nitride can enhance the heat resistance of the rubber matrix. In addition, silicon dioxide as a rigid particle will be exposed to the wear surface of the rubber matrix during the friction process with carbon nitride. When there is a sliding interface, the layered crystal structure of carbon nitride is easily sheared, thereby playing a lubricating role and improving the wear resistance of the rubber matrix.

[0036] In the present invention, a vinyl silane coupling agent is grafted onto the surface of a silicon dioxide / carbon nitride composite material, so that an antioxidant GM, N-phenylmaleimide and ethyl methacrylate can be copolymerized on the surface of the composite material through a carbon-carbon double bond reaction, thereby improving the compatibility and dispersibility of the composite material in a rubber matrix. In addition, the silicon dioxide / carbon nitride composite material is used as a carrier to reduce the migration of antioxidant substances. The obtained antioxidant has two antioxidant functional groups, namely, tertiary amine and hindered phenol, and has an enhanced antioxidant effect. At the same time, the antioxidant interacts with a carboxyl hydrogenated nitrile rubber matrix, thereby further improving the compatibility of the antioxidant with the matrix.

[0037] In the present invention, hydrogen-containing silicone oil is subjected to hydrosilylation with POSS having a carbon-carbon double bond and methyl methacrylate, so that POSS and methyl methacrylate are grafted in the hydrogen-containing silicone oil to obtain a modified silicone oil containing an ester group and POSS; the modified silicone oil is hydrolyzed under alkaline conditions to hydrolyze the ester group to form a carboxyl group, and the obtained carboxyl silicone oil is composite-vulcanized with hydrogenated carboxyl nitrile rubber, antioxidants and other additives to obtain a wear-resistant and heat-resistant rubber material. Among them, the carboxyl silicone oil has good interface compatibility with the hydrogenated carboxyl nitrile rubber due to its polar carboxyl group, and at the same time, since the carboxyl silicone oil is rich in siloxane segments, its molecular flexibility and low interface energy can improve the hydrophobicity and wear resistance of the wear-resistant and heat-resistant rubber material. In addition, carboxyl silicone oil has a Si-O-Si chain segment skeleton polyhedron structure of POSS, which can not only further improve the hydrophobicity and heat resistance of the rubber, but also open the silicon oxygen skeleton when the material encounters defects and damage to form a new skeleton structure. It has a certain self-repairing effect, which improves the mechanical properties and practicality of the rubber roller made of wear-resistant and heat-resistant rubber materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a process flow chart for preparing the wear-resistant and heat-resistant rubber roller in the present invention;

[0039] Figure 2 It is a line graph of the Akron abrasion test results of samples 1-8 prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention in the comprehensive performance test. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] This embodiment discloses a method for preparing a wear-resistant and heat-resistant rubber material, comprising the following steps:

[0043] Step (1), mixing carbon nitride nanosheets, water, and ethanol in a mass ratio of 1.2:300:1600 and ultrasonicating for 1 hour, adding hexadecyltrimethylammonium chloride and 28wt% ammonia water in sequence, and continuing ultrasonicating for 0.5 hour. After the ultrasonication, tetraethoxysilane is added dropwise for 20 minutes. After the addition is completed, the first reaction is carried out at room temperature for 24 hours. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, and water 5 times the mass of the filter cake is added for washing three times, and drying is carried out at 55°C for 8 hours to obtain a silicon dioxide / carbon nitride composite material;

[0044] The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and 28 wt % ammonia water is 10:0.5:40:300;

[0045] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane, and ethanol were mixed by ultrasound at a mass ratio of 1:8:100, 28 wt% ammonia water was added to adjust the pH value to 9, and the mixture was reacted for a second time at 35°C for 3 hours. After the reaction was completed, the mixture was centrifuged and filtered to obtain a filter cake, which was washed three times with water 5 times the mass of the filter cake, and dried at 55°C for 12 hours to obtain a modified silicon dioxide / carbon nitride composite material;

[0046] Step (2), uniformly mixing the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, wherein the mass ratio of the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 8:11:5:3.5:100:0.2, reacting in a nitrogen atmosphere at a temperature of 100° C. for 6 hours, filtering after the reaction, taking the filter cake, adding 5 times the mass of the filter cake to wash, and drying at a temperature of 50° C. for 18 hours to obtain an antioxidant;

[0047] Step (3), mixing heptaphenyl cage-like polysilsesquioxane trisilanol with tetrahydrofuran in a nitrogen atmosphere at a temperature of -3°C in a mass ratio of 1:10, adding triethylamine to mix evenly, dripping vinyltrichlorosilane solution, the dropping time is 25min, after the dropwise addition is completed, in a nitrogen atmosphere at a temperature of 5°C for a first reaction of 1.5h, after the reaction is completed, the second reaction is carried out at room temperature for 10h, after the reaction is completed, filtering, taking the filtrate, and removing the solvent tetrahydrofuran by rotary evaporation at a temperature of 55°C to obtain a crude reaction product, the crude reaction product and tetrahydrofuran are mixed and dissolved in a mass ratio of 1:6, and methanol precipitation equal to the mass of tetrahydrofuran is added, filtering, taking the filter cake, and drying at a temperature of 75°C for 9h to obtain modified POSS;

[0048] The mass ratio of heptaphenyl caged polysilsesquioxane trisilanol, triethylamine and vinyl trichlorosilane solution is 95:35:1050; the vinyl trichlorosilane solution is prepared by mixing vinyl trichlorosilane and tetrahydrofuran in a mass ratio of 1:5;

[0049] Mix hydrogenated silicone oil, toluene and chloroplatinic acid, add modified POSS and methyl methacrylate, the mass ratio of hydrogenated silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 8:30:0.05:0.8:0.8, react for the first time at 80°C in a nitrogen atmosphere for 16h, cool to room temperature after the reaction, remove the solvent toluene by rotary evaporation at 80°C, and dry at 70°C for 10h to obtain modified silicone oil;

[0050] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 80°C for 2.5h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 70°C for 48h to obtain a carboxyl silicone oil;

[0051] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil were mixed and kneaded at 110°C for 30 minutes, an antioxidant, magnesium stearate and white carbon black were added and mixed, and the kneading was continued at 110°C for 30 minutes, and a vulcanizing agent was added and mixed to obtain a wear-resistant and heat-resistant rubber material crude product, and vulcanized at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization, a wear-resistant and heat-resistant rubber material was obtained;

[0052] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 150:5:10:5:5:10, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 5:0.5:4.

[0053] Example 2

[0054] This embodiment discloses a method for preparing a wear-resistant and heat-resistant rubber material, comprising the following steps:

[0055] Step (1), mixing carbon nitride nanosheets, water, and ethanol in a mass ratio of 1.4:330:1700 and ultrasonicating for 1.2 hours, adding hexadecyltrimethylammonium chloride and 28wt% ammonia water in sequence, and continuing ultrasonicating for 0.6 hours. After the ultrasonication, tetraethoxysilane is added dropwise for 22 minutes. After the addition is completed, the first reaction is carried out at room temperature for 25 hours. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, and water 6 times the mass of the filter cake is added for washing three times, and then dried at 60°C for 10 hours to obtain a silicon dioxide / carbon nitride composite material;

[0056] The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and 28 wt % ammonia water is 12:0.8:50:380;

[0057] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane, and ethanol were mixed by ultrasound at a mass ratio of 1:8.5:120, 28 wt% ammonia water was added to adjust the pH value to 9.2, and the mixture was reacted for a second time at 36°C for 2.8 hours. After the reaction was completed, the mixture was centrifuged and filtered to obtain a filter cake, which was washed three times with water 6 times the mass of the filter cake, and dried at 60°C for 10 hours to obtain a modified silicon dioxide / carbon nitride composite material.

[0058] Step (2), uniformly mixing the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, wherein the mass ratio of the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 8.5:11:6:3.8:120:0.22, reacting in a nitrogen atmosphere at a temperature of 100° C. for 6 hours, filtering after the reaction, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at a temperature of 55° C. for 14 hours to obtain an antioxidant;

[0059] Step (3), mixing hydrogen-containing silicone oil, toluene and chloroplatinic acid, adding modified POSS and methyl methacrylate, the mass ratio of hydrogen-containing silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 8.5:35:0.05:0.85:0.85, reacting for the first time for 14 hours at 85°C in a nitrogen atmosphere, after the reaction is completed, cooling to room temperature, removing the solvent toluene by rotary evaporation at 85°C, and drying at 75°C for 9 hours to obtain modified silicone oil;

[0060] Wherein, the preparation of modified POSS is the same as that in Example 1;

[0061] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 85°C for 2.3h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 75°C for 45h to obtain a carboxyl silicone oil;

[0062] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil were mixed and kneaded at 115°C for 25 minutes, an antioxidant, magnesium stearate and white carbon black were added and mixed, the kneading was continued at 115°C for 25 minutes, a vulcanizing agent was added and mixed, and vulcanization was performed at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization was completed, a wear-resistant and heat-resistant rubber material was obtained;

[0063] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 140:5.5:12:6:6:9, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 6:0.6:4.5.

[0064] Example 3

[0065] This embodiment discloses a method for preparing a wear-resistant and heat-resistant rubber material, comprising the following steps:

[0066] Step (1), mixing carbon nitride nanosheets, water, and ethanol in a mass ratio of 1.6:350:1800 and ultrasonicating for 1.5 hours, adding hexadecyltrimethylammonium chloride and 28wt% ammonia water in sequence, and continuing ultrasonicating for 0.8 hours. After the ultrasonication, tetraethoxysilane is added dropwise for 25 minutes. After the addition is completed, the first reaction is carried out at room temperature for 27 hours. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, and water 6 times the mass of the filter cake is added for washing three times, and then dried at 60°C for 10 hours to obtain a silicon dioxide / carbon nitride composite material;

[0067] The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and 28 wt % ammonia water is 15:0.8:60:450;

[0068] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane, and ethanol were mixed by ultrasound at a mass ratio of 1:9:130, 28 wt% ammonia water was added to adjust the pH value to 9.5, and the mixture was reacted for a second time at 38°C for 2.5 hours. After the reaction was completed, the mixture was centrifuged and filtered to obtain a filter cake, which was washed three times with water 6 times the mass of the filter cake, and dried at 60°C for 10 hours to obtain a modified silicon dioxide / carbon nitride composite material.

[0069] Step (2), uniformly mixing the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, wherein the mass ratio of the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 9:12:6:4:130:0.25, reacting at 102° C. in a nitrogen atmosphere for 5.5 h. After the reaction is completed, filtering, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at 55° C. for 14 h to obtain an antioxidant;

[0070] Step (3), mixing hydrogen-containing silicone oil, toluene and chloroplatinic acid, adding modified POSS and methyl methacrylate, the mass ratio of hydrogen-containing silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 9:40:0.05:0.9:0.9, reacting for the first time for 14 hours at 85°C in a nitrogen atmosphere, after the reaction is completed, cooling to room temperature, removing the solvent toluene by rotary evaporation at 85°C, and drying at 75°C for 9 hours to obtain modified silicone oil;

[0071] Wherein, the preparation of modified POSS is the same as that in Example 1;

[0072] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 85°C for 2.3h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 75°C for 45h to obtain a carboxyl silicone oil;

[0073] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil were mixed and kneaded at 115°C for 25 minutes, an antioxidant, magnesium stearate and white carbon black were added and mixed, the kneading was continued at 115°C for 25 minutes, a vulcanizing agent was added and mixed, and vulcanization was performed at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization was completed, a wear-resistant and heat-resistant rubber material was obtained;

[0074] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 130:6:13:8:8:8, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 7:0.8:5.

[0075] Example 4

[0076] This embodiment discloses a method for preparing a wear-resistant and heat-resistant rubber material, comprising the following steps:

[0077] Step (1), mixing carbon nitride nanosheets, water, and ethanol in a mass ratio of 1.8:380:1900 and ultrasonicating for 1.8 hours, adding hexadecyltrimethylammonium chloride and 28wt% ammonia water in sequence, and continuing ultrasonicating for 1 hour. After the ultrasonication is completed, tetraethoxysilane is added dropwise for 25 minutes. After the addition is completed, the first reaction is carried out at room temperature for 28 hours. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, and water 6 times the mass of the filter cake is added for washing three times, and then dried at 60°C for 10 hours to obtain a silicon dioxide / carbon nitride composite material;

[0078] The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and 28 wt % ammonia water is 18:0.9:70:530;

[0079] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane, and ethanol were mixed by ultrasound at a mass ratio of 1:9.5:140, 28 wt% ammonia water was added to adjust the pH value to 10, and the mixture was reacted for a second time at 40°C for 2 hours. After the reaction was completed, the mixture was centrifuged and filtered to obtain a filter cake, which was washed three times with water 6 times the mass of the filter cake, and dried at 60°C for 10 hours to obtain a modified silicon dioxide / carbon nitride composite material;

[0080] Step (2), uniformly mixing the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, wherein the mass ratio of the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 9.5:14:6.5:4.3:140:0.28, reacting at 105° C. for 5 h in a nitrogen atmosphere, filtering after the reaction, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at 55° C. for 14 h to obtain an antioxidant;

[0081] Step (3), mixing hydrogen-containing silicone oil, toluene and chloroplatinic acid, adding modified POSS and methyl methacrylate, the mass ratio of hydrogen-containing silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 9.5:45:0.05:0.95:0.95, reacting for the first time for 14 hours at 85°C in a nitrogen atmosphere, after the reaction is completed, cooling to room temperature, removing the solvent toluene by rotary evaporation at 85°C, and drying at 75°C for 9 hours to obtain modified silicone oil;

[0082] Wherein, the preparation of modified POSS is the same as that in Example 1;

[0083] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 85°C for 2.3h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 75°C for 45h to obtain a carboxyl silicone oil;

[0084] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil are mixed and kneaded at 120°C for 20 minutes, an antioxidant, magnesium stearate and white carbon black are added and mixed, the kneading is continued at 120°C for 20 minutes, a vulcanizing agent is added and mixed, and vulcanization is performed at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization is completed, a wear-resistant and heat-resistant rubber material is obtained;

[0085] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 120:7:14:9:9:6, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 8:0.9:5.5.

[0086] Example 5

[0087] This embodiment discloses a method for preparing a wear-resistant and heat-resistant rubber material, comprising the following steps:

[0088] Step (1), mixing carbon nitride nanosheets, water, and ethanol in a mass ratio of 2:400:2000 and ultrasonicating for 2 hours, adding hexadecyltrimethylammonium chloride and 28wt% ammonia water in sequence, and continuing ultrasonicating for 1 hour. After the ultrasonication, tetraethoxysilane is added dropwise for 30 minutes. After the addition is completed, the first reaction is carried out at room temperature for 30 hours. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, and water 8 times the mass of the filter cake is added for washing three times, and then dried at 65°C for 12 hours to obtain a silicon dioxide / carbon nitride composite material;

[0089] The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and 28 wt % ammonia water is 20:1:80:600;

[0090] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane, and ethanol were mixed by ultrasound at a mass ratio of 1:10:150, 28 wt% ammonia water was added to adjust the pH value to 10, and the mixture was reacted for a second time at 40°C for 2 hours. After the reaction was completed, the mixture was centrifuged and filtered to obtain a filter cake, which was washed three times with water 8 times the mass of the filter cake, and dried at 65°C for 8 hours to obtain a modified silicon dioxide / carbon nitride composite material.

[0091] Step (2), uniformly mixing the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, wherein the mass ratio of the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 10:15:7:4.5:150:0.3, reacting in a nitrogen atmosphere at a temperature of 105°C for 5h, filtering after the reaction, taking the filter cake, adding water 8 times the mass of the filter cake for washing, and drying at a temperature of 60°C for 10h to obtain an antioxidant;

[0092] Step (3), mixing hydrogen-containing silicone oil, toluene and chloroplatinic acid, adding modified POSS and methyl methacrylate, the mass ratio of hydrogen-containing silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 10:50:0.05:1:1, reacting for the first time for 12h at 90°C in a nitrogen atmosphere, after the reaction is completed, cooling to room temperature, removing the solvent toluene by rotary evaporation at 90°C, and drying at 80°C for 8h to obtain modified silicone oil;

[0093] Wherein, the preparation of modified POSS is the same as that in Example 1;

[0094] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 90°C for 2h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 80°C for 42h to obtain a carboxyl silicone oil;

[0095] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil are mixed and kneaded at 120°C for 20 minutes, an antioxidant, magnesium stearate and white carbon black are added and mixed, the kneading is continued at 120°C for 20 minutes, a vulcanizing agent is added and mixed, and vulcanization is performed at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization is completed, a wear-resistant and heat-resistant rubber material is obtained;

[0096] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 100:8:15:10:10:5, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 9:1:6.

[0097] Example 6

[0098] This embodiment discloses a method for preparing a wear-resistant and heat-resistant rubber roller, comprising the following steps:

[0099] Add the wear-resistant and heat-resistant rubber material crude product into a twin-screw extruder and extrude it into a single-layer tube. At the same time, insert a stainless steel roller core into the center of the single-layer tube-shaped wear-resistant and heat-resistant rubber material crude product to obtain a rubber roller semi-finished product. After the rubber roller semi-finished product is vulcanized, it is polished and cut to obtain a wear-resistant and heat-resistant rubber roller.

[0100] The wear-resistant and heat-resistant rubber rollers prepared from the crude wear-resistant and heat-resistant rubber materials prepared in Examples 1-5 were respectively recorded as Samples 1-5, and the vulcanization conditions were: vulcanization at a pressure of 10 MPa and a temperature of 180° C. for 20 minutes.

[0101] Comparative Example 1

[0102] This comparative example discloses a method for preparing a rubber material, comprising the following steps:

[0103] Step (1), the antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene are mixed uniformly, azobisisobutyronitrile is added, the mass ratio of the antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 11:5:3.5:100:0.2, reacting for 6 hours at 100 ° C in a nitrogen atmosphere, after the reaction is completed, filtering, taking the filter cake, adding 5 times the mass of the filter cake for washing, and drying at 50 ° C for 18 hours to obtain an antioxidant;

[0104] Step (2), mixing hydrogen-containing silicone oil, toluene and chloroplatinic acid, adding modified POSS and methyl methacrylate, the mass ratio of hydrogen-containing silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 8:30:0.05:0.8:0.8, reacting for the first time for 16 hours at 80°C in a nitrogen atmosphere, after the reaction is completed, cooling to room temperature, removing the solvent toluene by rotary evaporation at 80°C, and drying at 70°C for 10 hours to obtain modified silicone oil;

[0105] Wherein, the preparation of modified POSS is the same as that in Example 1;

[0106] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 80°C for 2.5h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 70°C for 48h to obtain a carboxyl silicone oil;

[0107] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil were mixed and kneaded at 110°C for 30 minutes, an antioxidant, magnesium stearate and white carbon black were added and mixed, and the kneading was continued at 110°C for 30 minutes, a vulcanizing agent was added and mixed, and vulcanization was performed at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization was completed, a rubber material was obtained;

[0108] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 150:5:10:5:5:10, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 5:0.5:4.

[0109] Comparative Example 2

[0110] This comparative example discloses a method for preparing a rubber material, comprising the following steps:

[0111] Step (1), mixing carbon nitride nanosheets, water, and ethanol in a mass ratio of 1.2:300:1600 and ultrasonicating for 1 hour, adding hexadecyltrimethylammonium chloride and 28wt% ammonia water in sequence, and continuing ultrasonicating for 0.5 hour. After the ultrasonication, tetraethoxysilane is added dropwise for 20 minutes. After the addition is completed, the first reaction is carried out at room temperature for 24 hours. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, and water 5 times the mass of the filter cake is added for washing three times, and drying is carried out at 55°C for 8 hours to obtain a silicon dioxide / carbon nitride composite material;

[0112] The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and 28 wt % ammonia water is 10:0.5:40:300;

[0113] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane, and ethanol were mixed by ultrasound at a mass ratio of 1:8:100, 28 wt% ammonia water was added to adjust the pH value to 9, and the mixture was reacted for a second time at 35°C for 3 hours. After the reaction was completed, the mixture was centrifuged and filtered to obtain a filter cake, which was washed three times with water 5 times the mass of the filter cake, and dried at 55°C for 12 hours to obtain a modified silicon dioxide / carbon nitride composite material;

[0114] Step (2), uniformly mixing the modified silicon dioxide / carbon nitride composite material, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, wherein the mass ratio of the modified silicon dioxide / carbon nitride composite material, ethyl methacrylate, toluene, and azobisisobutyronitrile is 8:19.5:100:0.2, reacting in a nitrogen atmosphere at a temperature of 100° C. for 6 hours, filtering after the reaction, taking the filter cake, adding water 5 times the mass of the filter cake for washing, and drying at a temperature of 50° C. for 18 hours to obtain an antioxidant;

[0115] Step (3), mixing hydrogen-containing silicone oil, toluene and chloroplatinic acid, adding modified POSS and methyl methacrylate, the mass ratio of hydrogen-containing silicone oil, toluene, chloroplatinic acid, modified POSS and methyl methacrylate is 8:30:0.05:0.8:0.8, reacting for the first time for 16 hours at 80°C in a nitrogen atmosphere, after the reaction is completed, cooling to room temperature, removing the solvent toluene by rotary evaporation at 80°C, and drying at 70°C for 10 hours to obtain modified silicone oil;

[0116] Wherein, the preparation of modified POSS is the same as that in Example 1;

[0117] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 80°C for 2.5h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 70°C for 48h to obtain a carboxyl silicone oil;

[0118] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil were mixed and kneaded at 110°C for 30 minutes, an antioxidant, magnesium stearate and white carbon black were added and mixed, and the kneading was continued at 110°C for 30 minutes, a vulcanizing agent was added and mixed, and vulcanization was performed at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization was completed, a rubber material was obtained;

[0119] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 150:5:10:5:5:10, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 5:0.5:4.

[0120] Comparative Example 3

[0121] This comparative example discloses a method for preparing a rubber material, comprising the following steps:

[0122] Step (1), mixing carbon nitride nanosheets, water, and ethanol in a mass ratio of 1.2:300:1600 and ultrasonicating for 1 hour, adding hexadecyltrimethylammonium chloride and 28wt% ammonia water in sequence, and continuing ultrasonicating for 0.5 hour. After the ultrasonication, tetraethoxysilane is added dropwise for 20 minutes. After the addition is completed, the first reaction is carried out at room temperature for 24 hours. After the reaction is completed, centrifugation is performed, filtration is performed, a filter cake is taken, and water 5 times the mass of the filter cake is added for washing three times, and drying is carried out at 55°C for 8 hours to obtain a silicon dioxide / carbon nitride composite material;

[0123] The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane, and 28 wt % ammonia water is 10:0.5:40:300;

[0124] The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane, and ethanol were mixed by ultrasound at a mass ratio of 1:8:100, 28 wt% ammonia water was added to adjust the pH value to 9, and the mixture was reacted for a second time at 35°C for 3 hours. After the reaction was completed, the mixture was centrifuged and filtered to obtain a filter cake, which was washed three times with water 5 times the mass of the filter cake, and dried at 55°C for 12 hours to obtain a modified silicon dioxide / carbon nitride composite material;

[0125] Step (2), uniformly mixing the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, and toluene, adding azobisisobutyronitrile, wherein the mass ratio of the modified silica / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 8:11:5:3.5:100:0.2, reacting in a nitrogen atmosphere at a temperature of 100° C. for 6 hours, filtering after the reaction, taking the filter cake, adding 5 times the mass of the filter cake to wash, and drying at a temperature of 50° C. for 18 hours to obtain an antioxidant;

[0126] Step (3), mixing hydrogen-containing silicone oil, toluene and chloroplatinic acid, adding methyl methacrylate, the mass ratio of hydrogen-containing silicone oil, toluene, chloroplatinic acid and methyl methacrylate is 8:30:0.05:1.6, reacting for the first time at 80° C. in a nitrogen atmosphere for 16 hours, cooling to room temperature after the reaction, removing the solvent toluene by rotary evaporation at 80° C., and drying at 70° C. for 10 hours to obtain modified silicone oil;

[0127] The modified silicone oil was mixed with a 20wt% sodium hydroxide aqueous solution at a mass ratio of 2:1, and the mixture was reacted for a second time at 80°C for 2.5h. After the reaction was completed, the mixture was cooled to room temperature, a 1mol / L hydrochloric acid aqueous solution was added to adjust the pH value to neutral, and the mixture was dried at 70°C for 48h to obtain a carboxyl silicone oil;

[0128] The hydrogenated carboxyl nitrile rubber and carboxyl silicone oil were mixed and kneaded at 110°C for 30 minutes, an antioxidant, magnesium stearate and white carbon black were added and mixed, and the kneading was continued at 110°C for 30 minutes, a vulcanizing agent was added and mixed, and vulcanization was performed at a pressure of 10MPa and a temperature of 180°C for 20 minutes. After the vulcanization was completed, a rubber material was obtained;

[0129] Among them, the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizer is 150:5:10:5:5:10, and the vulcanizer is prepared by mixing sulfur vulcanizer, diisopropylbenzene peroxide and zinc oxide in a mass ratio of 5:0.5:4.

[0130] Comparative Example 4

[0131] This comparative example discloses a method for preparing a rubber roller, comprising the following steps:

[0132] The wear-resistant and heat-resistant rubber material crude product is added into a twin-screw extruder and extruded into a single-layer tube. At the same time, a stainless steel roller core is inserted into the center of the single-layer tube-shaped wear-resistant and heat-resistant rubber material crude product to obtain a rubber roller semi-finished product. The rubber roller semi-finished product is vulcanized. After the vulcanization is completed, it is polished and cut to obtain a rubber roller.

[0133] The rubber rollers prepared using the crude rubber materials prepared in Comparative Examples 1-3 as raw materials were recorded as samples 6-8 respectively, and the vulcanization conditions were: vulcanization at a pressure of 10 MPa and a temperature of 180° C. for 20 minutes.

[0134] In the above embodiments and comparative examples: carbon nitride nanosheets are from Xi'an Ruixi Biotechnology Co., Ltd., the model is few-layer graphite phase carbon nitride nanosheets, the average number of layers is less than 10, the thickness is 1-3nm, and the particle size is 10-15μm; ethanol is from Shanghai Yishi Chemical Co., Ltd., CAS No.: 64-17-5; hexadecyltrimethylammonium chloride is from Wuhan Jixin Yibang Biotechnology Co., Ltd., CAS No.: 112-02-7; ammonia water is from Shandong Tenghua New Materials Co., Ltd., with a concentration of 28wt%; tetraethoxysilane is from Shandong Guohua Chemical Co., Ltd., CAS No.: 78-10-4; Vinyl trimethoxysilane was from Shandong Shouhua Chemical Co., Ltd., CAS No.: 2768-02-7; antioxidant GM was from Nanjing Milan Chemical Co., Ltd., model antioxidant 3052, product name 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylphenyl)methyl-4-methylphenyl acrylate, CAS No.: 61167-58-6; N-phenylmaleimide was from Hubei Wei's Chemical Reagent Co., Ltd., CAS No.: 941-69-5; ethyl methacrylate was from Shanghai Hongzhuang Chemical Technology Co., Ltd., CAS No.: 97-63-2; toluene was from from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 108-88-3; azobisisobutyronitrile from Shandong Ranxi Chemical Technology Co., Ltd., CAS No.: 78-67-1; heptaphenyl caged polysilsesquioxane trisilanol from Angxing New Carbon Materials Changzhou Co., Ltd., CAS No.: 444315-26-8; tetrahydrofuran from Guangzhou Jiatu Technology Co., Ltd., CAS No.: 109-99-9; triethylamine from Jinan Century Tongda Chemical Co., Ltd., CAS No.: 121-44-8; vinyl trichlorosilane from Shandong Poly Chemical Co., Ltd., CAS No.: 75- 94-5; methanol from Dongguan Xunye Chemical Reagent Co., Ltd., CAS No.: 67-56-1; hydrogen-containing silicone oil from Hubei Longsheng Sihai New Materials Co., Ltd., with a hydrogen content of 1.6%; chloroplatinic acid from Shandong Guohua Chemical Co., Ltd., CAS No.: 16941-12-1; sodium hydroxide from Wuxi Jingke Chemical Co., Ltd., CAS No.: 1310-73-2; hydrochloric acid aqueous solution from Shanghai Yuanye Biotechnology Co., Ltd., item No. B62243, model hydrogen chloride standard solution; hydrogenated carboxylated nitrile rubber (XHNBR) from German Lanxess, brand Therban XT VP KA 8889, containing 33% acrylonitrile, 5% carboxyl and 3.5% carbon-carbon double bonds; magnesium stearate comes from Shandong Shoucheng Chemical Co., Ltd., CAS number: 557-04-0; white carbon black comes from Foshan Jieke New Materials Co., Ltd., brand Japan Tosoh, model white carbon black LP, CAS number: 10279-57-9; sulfur vulcanizer comes from Guangdong Zhanlin Chemical Co., Ltd., model Zhanlin IS90-75 rubber vulcanizer; diisopropylbenzene peroxide comes from Shanghai Bojing Chemical Co., Ltd., CAS number: 80-43-3; zinc oxide comes from Shandong Duoju Chemical Co., Ltd., CAS number: 1314-13-2; stainless steel roller core comes from Yangzhou Wanlida Roller Co., Ltd., Vickers hardness is HV88-90. .

[0135] Test example

[0136] The wear-resistant and heat-resistant rubber materials prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to performance tests, and the specific test results are shown in Table 1; the comprehensive performance tests were conducted on Samples 1-8 prepared in Example 6 and Comparative Example 4, and the specific test results are shown in Table 2:

[0137] Table 1

[0138]

[0139]

[0140] Table 2

[0141]

[0142] The tests of various indicators in Table 1 and Table 2 are based on the following standards: tensile strength is measured according to the standard GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; hardness is measured according to the standard GB / T531.1-2008 "Test method for indentation strength of vulcanized rubber or thermoplastic rubber Part 1: Shore durometer method (Shore hardness)"; Akron abrasion is measured according to the standard GB / T1689-1998 "Determination of tensile stress-strain properties of vulcanized rubber" The heat aging performance is measured according to the standard GB / T3512-2001 "Hot air accelerated aging and heat resistance test for vulcanized rubber or thermoplastic rubber"; the static compression deformation rate is measured according to the standard GB / T1687-1993 "Determination of temperature rise and fatigue resistance of vulcanized rubber in flexure test Part 2: Compression flexure test"; the impact elasticity is measured according to the standard GB / T1681-2009 "Determination of the rebound elasticity of vulcanized rubber".

[0143] The wear-resistant and heat-resistant rubber material prepared by the invention has excellent wear resistance and heat resistance and excellent comprehensive performance. The wear-resistant and heat-resistant rubber roller prepared by the wear-resistant and heat-resistant rubber material can be used for spinning Lyocell.

[0144] In the present invention, silicon dioxide is in-situ grown on carbon nitride by a sol-gel method to obtain a silicon dioxide / carbon nitride composite material. The introduction of silicon dioxide improves the hardness of carbon nitride and constructs a rough microscopic interface on the surface of carbon nitride, thereby improving its compatibility with the rubber matrix. At the same time, the heat resistance of silicon dioxide and the thermal conductivity of carbon nitride can enhance the heat resistance of the rubber matrix. In addition, silicon dioxide as a rigid particle and carbon nitride will be exposed to the wear surface of the rubber matrix during the friction process. When there is a sliding interface, the layered crystal structure of carbon nitride is easily sheared, thereby playing a lubricating role and improving the wear resistance of the rubber matrix. In Comparative Example 1, no silicon dioxide / carbon nitride composite material is added, and silicon dioxide and carbon nitride are lacking as composite wear-resistant materials to play a lubricating and wear-resistant role on the rubber matrix and increase thermal conductivity and heat resistance, so the wear resistance and thermal oxidation resistance are reduced.

[0145] In the present invention, a vinyl silane coupling agent is grafted onto the surface of the silica / carbon nitride composite material, so that the antioxidant GM, N-phenylmaleimide, and ethyl methacrylate can be copolymerized on the surface of the composite material through a carbon-carbon double bond reaction, thereby improving the compatibility and dispersibility of the composite material in the rubber matrix. The silica / carbon nitride composite material is used as a carrier to reduce the migration of antioxidant substances. The obtained antioxidant has two antioxidant functional groups, tertiary amine and hindered phenol, and the antioxidant effect is enhanced. At the same time, the antioxidant interacts with the carboxyl hydrogenated nitrile rubber matrix, further improving the compatibility of the antioxidant with the matrix. In Comparative Example 2, the silica / carbon nitride composite material is not copolymerized with the antioxidant monomer, and the obtained antioxidant does not have two antioxidant functional groups, tertiary amine and hindered phenol, to play an antioxidant aging role on the rubber matrix, so the antioxidant capacity decreases.

[0146] In the present invention, hydrogenated silicone oil is subjected to hydrosilylation with POSS and methyl methacrylate having a carbon-carbon double bond, so that POSS and methyl methacrylate are grafted in hydrogenated silicone oil to obtain a modified silicone oil containing an ester group and POSS; the modified silicone oil is hydrolyzed under alkaline conditions to hydrolyze the ester group to form a carboxyl group, and the obtained carboxyl silicone oil is composite-vulcanized with auxiliary agents such as hydrogenated carboxyl nitrile rubber and antioxidants to obtain a wear-resistant and heat-resistant rubber material. Among them, carboxyl silicone oil has good interfacial compatibility with hydrogenated carboxyl nitrile rubber due to its polar carboxyl group, and its molecular flexibility and low interfacial energy can improve the wear resistance of the wear-resistant and heat-resistant rubber material. In addition, the carboxyl silicone oil has a polyhedral structure of the Si-O-Si segment skeleton of POSS, and this structure can further improve the heat resistance of the composite rubber. In comparative example 3, carboxyl silicone oil is not grafted with modified POSS, and the obtained carboxyl silicone oil lacks the rigid structure of POSS, and the heat resistance is reduced, so the thermal oxidation resistance of the material is reduced.

[0147] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a wear-resistant and heat-resistant rubber material, characterized in that: The following steps are involved: Step (1), mixing carbon nitride nanosheets, water and ethanol with ultrasound, adding hexadecyltrimethylammonium chloride and ammonia water in sequence, and continuing ultrasound. After the ultrasound is completed, tetraethoxysilane is added dropwise. After the addition is completed, the mixture is reacted. After the reaction is completed, the mixture is centrifuged, filtered, a filter cake is taken, washed, and dried to obtain a silicon dioxide / carbon nitride composite material; The mass ratio of carbon nitride nanosheets, hexadecyltrimethylammonium chloride, tetraethoxysilane and ammonia water is 10-20:0.5-1:40-80:300-600, and the ammonia water is 28wt% ammonia water; the dripping time of tetraethoxysilane is 20-30min; the reaction conditions are: the first reaction is carried out at room temperature for 24-30h; The silicon dioxide / carbon nitride composite material, vinyltrimethoxysilane and ethanol are mixed by ultrasonication, a regulator is added to adjust the pH value, and the mixture is reacted. After the reaction is completed, the mixture is centrifuged, filtered, the filter cake is collected, washed and dried to obtain a modified silicon dioxide / carbon nitride composite material; The mass ratio of the silicon dioxide / carbon nitride composite material, vinyl trimethoxysilane and ethanol is 1:8-10:100-150; the reaction conditions are: a second reaction at a pH value of 9-10 and a temperature of 35-40° C. for 2-3 hours; The modified silicon dioxide / carbon nitride composite material, antioxidant GM, N-phenylmaleimide, ethyl methacrylate and toluene are uniformly mixed, and azobisisobutyronitrile is added to react. After the reaction is completed, the filter is filtered, the filter cake is taken, washed and dried to obtain an antioxidant; Step (2), mixing hydrogen-containing silicone oil, toluene, and chloroplatinic acid, adding modified POSS and methyl methacrylate, reacting for the first time, cooling after the reaction is completed, removing the solvent toluene by rotary evaporation, and drying to obtain modified silicone oil; mixing the modified silicone oil with a sodium hydroxide aqueous solution, reacting for the second time, cooling after the reaction is completed, adding a regulator to adjust the pH value, and drying to obtain carboxyl silicone oil; The hydrogenated carboxyl nitrile rubber is mixed with the carboxyl silicone oil, and the mixture is mixed with an antioxidant, magnesium stearate, and white carbon black. The mixture is further mixed with a vulcanizing agent to obtain a crude wear-resistant and heat-resistant rubber material, and the mixture is vulcanized. After the vulcanization is completed, a wear-resistant and heat-resistant rubber material is obtained.

2. The method for preparing a wear-resistant and heat-resistant rubber material according to claim 1, characterized in that: In the step (1), the mass ratio of the modified silicon dioxide / carbon nitride composite material, the antioxidant GM, N-phenylmaleimide, ethyl methacrylate, toluene, and azobisisobutyronitrile is 8-10:11-15:5-7:3.5-4.5:100-150:0.2-0.3; and the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 100-105° C. for 5-6 hours.

3. The method for preparing a wear-resistant and heat-resistant rubber material according to claim 1, characterized in that: In the step (2), the modified POSS used for preparing the carboxyl silicone oil comprises the following steps: Heptaphenyl caged polysilsesquioxane trisilanol is mixed with tetrahydrofuran, triethylamine is added and mixed evenly, vinyl trichlorosilane solution is added dropwise, and after the addition is completed, a first reaction is performed, and after the reaction is completed, a second reaction is performed, and after the reaction is completed, purification is performed to obtain modified POSS; Among them, the mixing conditions of heptaphenyl caged polysilsesquioxane trisilanol and tetrahydrofuran are: mixing in a nitrogen atmosphere at a temperature of -5-0°C; the dropping time of the vinyltrichlorosilane solution is 20-30min; the mass ratio of heptaphenyl caged polysilsesquioxane trisilanol, triethylamine, and vinyltrichlorosilane solution is 90-100:30-40:1000-1100; the first reaction conditions are: the first reaction is carried out in a nitrogen atmosphere at a temperature of 0-10°C for 1-2h; the second reaction conditions are: the second reaction is carried out at room temperature for 8-10h.

4. The method for preparing a wear-resistant and heat-resistant rubber material according to claim 1, characterized in that: In the step (2), when preparing carboxyl silicone oil: the mass ratio of hydrogenated silicone oil, toluene, chloroplatinic acid, modified POSS, and methyl methacrylate is 8-10:30-50:0.05:0.8-1:0.8-1; the first reaction conditions are: in a nitrogen atmosphere, at a temperature of 80-90° C., for 12-16 hours.

5. The method for preparing a wear-resistant and heat-resistant rubber material according to claim 1, characterized in that: In the step (2), when preparing the carboxyl silicone oil, the mass ratio of the modified silicone oil to the sodium hydroxide aqueous solution is 2:1, and the sodium hydroxide aqueous solution is a 20wt% sodium hydroxide aqueous solution; the second reaction conditions are: the second reaction is carried out at a temperature of 80-90°C for 2-2.5h.

6. The method for preparing a wear-resistant and heat-resistant rubber material according to claim 1, characterized in that: In the step (2), the mass ratio of hydrogenated carboxyl nitrile rubber, carboxyl silicone oil, antioxidant, magnesium stearate, white carbon black and vulcanizing agent is 100-150:5-8:10-15:5-10:5-10:5-10; the vulcanizing agent is prepared by mixing sulfur vulcanizing agent, dicumyl peroxide and zinc oxide in a mass ratio of 5-9:0.5-1:4-6; The mixing conditions are: mixing and mixing at 110-120°C for 20-30 minutes; the continued mixing conditions are: continuing mixing at 110-120°C for 20-30 minutes; the vulcanization conditions are: vulcanization at a pressure of 10MPa and a temperature of 170-190°C for 15-25 minutes.

7. A wear-resistant and heat-resistant rubber material prepared by the method for preparing a wear-resistant and heat-resistant rubber material as claimed in any one of claims 1 to 6.

8. A wear-resistant and heat-resistant rubber roller prepared based on the wear-resistant and heat-resistant rubber material crude product as claimed in any one of claims 1 to 6.

9. Use of the wear-resistant and heat-resistant rubber roller as claimed in claim 8 in spinning lyocell.

Citation Information

Patent Citations

  • Rubber compound of spinning rubber roll

    CN105906885A

  • Production formula of rubber roller for lyocell fiber spinning

    CN113583317A

  • High-heat-resistance degradable modified polystyrene foam packaging material and preparation method thereof

    CN111763347A

  • Wear-resistant and aging-resistant natural rubber material and preparation method thereof

    CN114456453A